Concepts of Semiconductor Photocatalysis - Rahman, Mohammed; Khan, Anish; Asiri, Abdullah; Inamuddin, Inamuddin (IntechOpen, 2019)
This book "Concepts of Semiconductor Photocatalysis" contains recent research on the preparation, characterization, and potential applications of the semiconductor photocatalyst. This research is promising and has received a lot of interest in the last few decades. The book covers advanced topics on the optical, physical, structural, and electro-catalysis and photo-catalysis applications. Development of new and noble efficient technology is pointing researchers toward the safe, facile, non-toxic, eco-friendly route of synthesis-to-applications, which can be used for manufacture at a large scale. This book presents an overview of the current photocatalyst fundamental theory, substantial applications, and use of the research worldwide. It is an important book for research organizations, government research-centers, academic libraries, and R&D affianced in recent research and development of doped or undoped low dimensional semiconductor photocatalysts.